Positive electrode material and preparation method, positive electrode sheet and preparation method and application

By covering the solid electrolyte layer with a larger electrochemical window on the positive electrode material of the secondary battery, the problem of poor stability of the positive electrode material under high voltage conditions is solved, and higher electrochemical stability and battery performance are achieved.

CN116093276BActive Publication Date: 2025-02-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211515930.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-02-18
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

The positive electrode material of traditional secondary battery has poor stability under high voltage conditions, which limits the use of batteries under high voltage conditions.

Method used

A positive electrode material including an active material and a solid electrolyte layer coated on the surface of the active material is adopted. The electrochemical window of the solid electrolyte layer is larger than the electrochemical window of the active material to improve the stability of the positive electrode material.

Benefits of technology

Through the introduction of the solid electrolyte layer, the electrochemical window of the positive electrode material is effectively improved, the irreversible change of the lattice is suppressed, the stability of the positive electrode material under high voltage conditions is improved, and the performance of the battery under high voltage conditions is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116093276B_ABST
    Figure CN116093276B_ABST
Patent Text Reader

Abstract

The present application provides a positive electrode material and preparation method, a positive electrode sheet and preparation method, a secondary battery, a battery module, a battery pack and an electrical device. The positive electrode material includes an active material and a solid electrolyte layer coated on the surface of the active material; the electrochemical window of the solid electrolyte layer is larger than the electrochemical window of the active material. In the positive electrode material, the introduction of the solid electrolyte layer effectively improves the electrochemical window of the positive electrode material, which can inhibit the irreversible change of the lattice of the positive electrode material during the lithium insertion and extraction process, so that the positive electrode material maintains a stable structure, thereby improving the stability of the positive electrode material under high voltage conditions and improving the performance of the battery under high voltage conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode material and a preparation method, a positive electrode sheet and a preparation method, a secondary battery, a battery module, a battery pack, and an electrical device. Background Art

[0002] Secondary batteries have the characteristics of high energy density and are relatively environmentally friendly. With the continuous increase in consumer demand, the stable performance of batteries under high voltage conditions has gradually become a common demand. For traditional secondary batteries, the stability of their positive electrode materials under high voltage conditions is poor, which restricts the use of batteries under high voltage conditions. Summary of the invention

[0003] The present application provides a positive electrode material, comprising an active material and a solid electrolyte layer coated on the surface of the active material; the electrochemical window of the solid electrolyte layer is larger than the electrochemical window of the active material.

[0004] In the above-mentioned positive electrode materials, the introduction of the solid electrolyte layer effectively improves the electrochemical window of the positive electrode material, which can inhibit the irreversible change of the lattice of the positive electrode material during the lithium insertion and extraction process, so that the positive electrode material maintains a stable structure, thereby improving the stability of the positive electrode material under high voltage conditions and improving the performance of the battery under high voltage conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0005] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0006] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0007] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0008] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0009] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0010] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0011] Description of reference numerals:

[0012] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module; 5. Secondary battery; 51. Shell; 52. Electrode assembly; 53. Top cover assembly. DETAILED DESCRIPTION

[0013] Below, the battery assembly, battery cell, secondary battery and electric device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0014] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0015] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0016] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0017] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0018] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0019] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true or exists, and B is false or does not exist; A is false or does not exist, and B is true or exists; or both A and B are true, or both A and B exist.

[0020] If there is no special explanation, in this application, the terms "positive electrode sheet" and "positive electrode sheet" have the same meaning and can be used interchangeably. The terms "negative electrode sheet" and "negative electrode sheet" have the same meaning and can be used interchangeably. The terms "diaphragm" and "separation membrane" have the same meaning and can be used interchangeably.

[0021] The present application provides a positive electrode material. The positive electrode material includes an active material and a solid electrolyte layer coated on the surface of the active material; the electrochemical window of the solid electrolyte layer is larger than the electrochemical window of the active material. In the positive electrode material, the electrochemical window of the positive electrode material is effectively improved by introducing the solid electrolyte layer, and the irreversible change of the lattice of the positive electrode material during the lithium insertion and extraction process can be suppressed, so that the positive electrode material maintains a stable structure, thereby improving the stability of the positive electrode material under high voltage conditions and improving the performance of the battery under high voltage conditions.

[0022] It can be understood that under high voltage conditions, the stability of the positive electrode material in the present application is effectively improved. For a battery including the positive electrode material, its charge and discharge voltage window is also effectively improved, which can give the battery a higher charge and discharge capacity, thereby providing a new direction for the development of high-capacity batteries.

[0023] At the same time, during the charge and discharge process of the secondary battery, the positive electrode active material will inevitably produce a certain amount of transition metal ions. For example, when the positive electrode material undergoes irreversible changes in the lattice during the lithium insertion and extraction process, or when the battery includes an electrolyte, the positive electrode material is easily affected by the H in the electrolyte. 2 A certain amount of transition metal ions may be produced during the corrosion of O and HF. Transition metal ions easily migrate to the surface of the negative electrode and are reduced to metals. The metals easily catalyze the decomposition of the SEI film and consume active lithium, thereby causing deterioration of electrical performance. In the positive electrode material of the present application, the solid electrolyte layer can reduce the content of transition metal ions through chemical reactions or adsorption reactions, such as by complexing with transition metal ions to avoid the overflow of transition metal ions, thereby reducing the content of transition metal ions inside the battery and improving the electrical performance of the secondary battery.

[0024] It is understood that the present application has no particular limitation on the type of active material, and any known active material may be selected. Alternatively, the active material in the present application may be selected from the positive electrode active materials listed below.

[0025] In one embodiment, the electrochemical window of the solid electrolyte layer is ≥5V. This can provide good protection for the positive electrode material under high voltage conditions, so that the positive electrode material can still maintain good structural stability under a high voltage of 4.4V. Optionally, the electrochemical window of the solid electrolyte layer is ≥5.1V. Optionally, the electrochemical window of the solid electrolyte layer is ≥5.2V.

[0026] It is understandable that the electrochemical window test is carried out using the linear voltammetric test module of the electrochemical workstation. The material to be tested and the binder PVDF are mixed in a mass ratio of 95:5 and drop-coated on the surface of the glassy carbon electrode as the working electrode. 6 The voltammetric curve is tested as a solution and a lithium sheet as a counter electrode in a voltage range of 2.5 to 5 V and a scan rate of 0.5 mV / s. The oxidation potential is recorded as the electrochemical window. It is understood that when the electrochemical window of the solid electrolyte layer needs to be measured, the material to be tested is a solid electrolyte. When the electrochemical window of the active material needs to be measured, the material to be tested is an active material.

[0027] In one embodiment, the lithium ion conductivity of the solid electrolyte layer is ≥ 0.8×10 -4 mS / cm. At this time, it helps lithium ions to migrate quickly inside the solid electrolyte layer and improve the cycle performance of the battery.

[0028] It can be understood that the ionic conductivity measurement method: the AC impedance test uses the electrochemical workstation impedance test module, voltage perturbation mode PEIS, perturbation voltage 5mV, frequency range 200kHZ ~ 30mHZ, to perform impedance test on the solid electrolyte sheet and calculate the ionic conductivity of the electrolyte sheet.

[0029] Specifically, solid electrolytes are ion conductors and are not conductive to electrons. Therefore, before impedance testing, it is necessary to connect blocking Ag electrodes on both sides of the solid electrolyte sheet: polish both sides of the sintered solid electrolyte to a certain thickness, apply silver paste to lead out Ag wires, and sinter Ag in a muffle furnace to make the Ag electrode in close contact with the electrolyte surface. Measure the resistance R = h / (ρs) and solve for the ionic conductivity σ, where σ = 1 / ρ.

[0030] In one embodiment, the thickness of the solid electrolyte layer is 0.5nm to 5nm. The thickness of the solid electrolyte layer is within this range, which allows the battery to have low impedance, good cycle stability and good rate performance. Optionally, the thickness of the solid electrolyte layer is 1nm to 4nm. Optionally, the thickness of the solid electrolyte layer is 1nm to 3nm. Optionally, the thickness of the solid electrolyte layer is 1nm to 2nm. Optionally, the thickness of the solid electrolyte layer can be but is not limited to 0.5nm, 1nm, 1.5nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm or 5nm, etc. It is understandable that the thickness of the solid electrolyte layer can also be other suitable choices within the range of 0.5nm to 5nm.

[0031] In one embodiment, the solid electrolyte layer includes a chemical composition of Li a MX a+3 A material wherein 1≤a≤6; M is selected from cations of one or more of the following elements: Al, Ga, In, Y, Zr, Nb, Sc, Ti, Mn, and La series elements; and X is selected from anions containing one or more of the following elements: halogen, S, O, and P.

[0032] Optionally, when X is a halogen anion, the halogen element can migrate into the interior of the positive electrode material to form a transition layer, thereby reducing the migration energy of Li ions and stabilizing lattice oxygen, further improving the lithium ion conductivity and structural stability of the positive electrode material.

[0033] In one embodiment, 2≤a≤4. Optionally, a=3. In addition, a can represent an integer or a non-integer. As some optional examples of a, a can be 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5, 5.2, 5.5, 5.8, 6, etc. It is understandable that a can also be selected in other ranges of 1 to 6.

[0034] In one embodiment, M is a +3 cation. For example, M includes Al 3+ , Ga 3+ 、In 3+ , Y 3+ 、Zr 3+ , Nb 3 + Sc 3+ 、Ti 3+ , Mn 3+ , La-based elements +3 cations. Optionally, M includes Al 3+ , Ga 3+ 、In 3+ , Y 3+ 、Zr 3+ , Nb 3+ Sc 3+ 、Ti 3+ , Mn 3+ , Er 3+ , Tb 3+ , Yb 3+ 、Lu 3+ ,La 3+ and Ho 3+ In addition, as an optional example of X, X includes F - , Cl - Br - ,I - , S 2- , O 2- and PO 4 - One or more of .

[0035] In one embodiment, the solid electrolyte layer includes Li 3 InF 6 , Li 3 YF 6 , Li 3 S F 6 , Li 3 Mn 6 , Li 3 ZF 6 , Li 3 YF6 , Li 3 InCl 6 , Li 3 YC 6 , Li 3 ScCl 6 , Li 3 MnCl 6 , Li 3 ZrCl 6 and Li 3 YC 6 At least one of .

[0036] The present application also provides a method for preparing a positive electrode material. The method for preparing a positive electrode material comprises the following steps: forming a solid electrolyte layer on the surface of an active material; wherein the electrochemical window of the solid electrolyte layer is greater than the electrochemical window of the active material. The atomic deposition method is a method for chemical vapor deposition of thin films based on ordered surface self-saturation, which can form a deposition layer of several atoms thick on the surface of the positive electrode material to achieve uniform coating. A solid electrolyte layer with small thickness and good uniformity can be obtained by the atomic deposition method.

[0037] In one embodiment, a solid electrolyte layer is formed on the surface of the active material by an atomic deposition method. Optionally, forming the solid electrolyte layer on the surface of the active material comprises the following steps: in a protective gas atmosphere, a gas phase Li source, a gas phase X source and a gas phase M source are sequentially introduced into the dispersed active material to form a solid electrolyte layer having a chemical composition of Li on the surface of the active material. a MX a+3 A solid electrolyte layer of a material of , wherein 1≤a≤6, M is selected from cations of one or more of the following elements: Al, Ga, In, Y, Zr, Nb, Sc, Ti, Mn, and La series elements; X is selected from anions containing one or more of the following elements: halogen, S, O, and P. In this embodiment, a gas-phase Li source, a gas-phase X source, and a gas-phase M source are sequentially introduced into the dispersed active material. When the gas-phase Li source, the gas-phase X source, and the gas-phase M source contact the active material, chemical adsorption and surface reaction occur on the surface of the active material, thereby forming a solid electrolyte layer with a small thickness and good uniformity on the surface of the active material.

[0038] It is understood that the formation of dispersed active material can be achieved by blowing protective gas on active material particles to disperse the active material, thereby forming dispersed active material. It is understood that atomic deposition can be performed in a fluidized bed reactor to form a solid electrolyte layer on the surface of the active material.

[0039] Optionally, the protective gas may be one or more of nitrogen, helium, neon, argon and xenon.

[0040] In one embodiment, a gas-phase Li source, a gas-phase X source, and a gas-phase M source are sequentially introduced into the dispersed active material, and then the gas-phase Li source, the gas-phase X source, and the gas-phase M source are repeatedly introduced in sequence. By introducing the gas-phase Li source, the gas-phase X source, and the gas-phase M source multiple times, the thickness of the solid electrolyte layer on the surface of the active material can be accurately controlled. For example, introducing the gas-phase Li source, the gas-phase X source, and the gas-phase M source once can be regarded as a cycle number, and a solid electrolyte layer with a thickness of 0.1 nm is formed on the surface of the active material. Then, one or more cycles are performed to obtain a solid electrolyte layer that meets the required thickness.

[0041] It is understandable that before the gas-phase Li source is introduced, the reaction environment can be cleaned with a protective gas so that the solid electrolyte can be better coated on the surface of the active material.

[0042] In one embodiment, the temperature of the protective gas atmosphere is 150°C to 250°C. It is understood that in this embodiment, the temperature of the protective gas atmosphere represents the reaction temperature for atomic deposition. Optionally, the temperature of the protective gas atmosphere can be but is not limited to 150°C, 180°C, 200°C, 220°C, 250°C, etc. It is understood that the temperature of the protective gas atmosphere can also be other suitable selections within the range of 150°C to 250°C.

[0043] In one embodiment, the reaction system is purged by a protective gas in the gaps between the gas-phase Li source, the gas-phase X source and the gas-phase M source. The reaction system is purged by a protective gas after each introduction of the gas-phase Li source, the reaction system is purged by a protective gas after each introduction of the gas-phase X source, and the reaction system is purged by a protective gas after each introduction of the gas-phase M source. Optionally, the time for each purge is 10s to 20s. For example, the time for each purge may be, but is not limited to, 10s, 12s, 15s, 17s, 19s, 20s, etc. It is understandable that the time for each purge may also be other suitable choices within the range of 10s to 20s.

[0044] In one embodiment, the ratio of the injection pulses of the gas phase Li source, the gas phase X source and the gas phase M source is a:(a+3):1. It can be understood that the injection pulse means that the material is injected sequentially for a continuous injection time each time. By controlling the injection pulses of the gas phase Li source, the gas phase X source and the gas phase M source, the Li in the solid electrolyte layer can be adjusted. a MX a+3 The concentration distribution forms a gradient coating, which can more accurately control the coating of the solid electrolyte layer and obtain a solid electrolyte with better uniformity. Optionally, the injection pulses of the gas-phase Li source, the gas-phase X source and the gas-phase M source are 3s, 6s and 1s respectively.

[0045] It can be understood that the initial state of the Li source, X source and M source is a condensed state. When the solid electrolyte layer is formed on the surface of the active material by the atomic deposition method, the condensed Li source, X source and M source are respectively vaporized to form a gas-phase Li source, a gas-phase X source and a gas-phase M source, and then react with the surface of the active material in the form of a gas.

[0046] Alternatively, the Li source is selected from one or more of alkyl lithium, lithium carboxylate, lithium alcoholate and lithium ester. Further optionally, the Li source is selected from one or more of methyl lithium, n-butyl lithium and lithium tert-butoxide. Alternatively, the X source is selected from one or more of halogenated alkanes, halogenated carboxylic acids, halogenated alcohols and halogenated esters. Further optionally, the X source is selected from one or more of fluoroalkanes, fluorocarboxylic acids, fluoroalcohols and fluoroesters. Further optionally, the X source is selected from fluoroethylene carbonate. Alternatively, the M source is selected from one or more of alkyl metals, carboxylic acid metals, alcohol metals and ester metals.

[0047] Optionally, the boiling point of the Li source is between 70°C and 300°C. The boiling point of the X source is between 70°C and 300°C. The boiling point of the M source is between 70°C and 300°C.

[0048] In one embodiment, the preparation method of the positive electrode material further includes: performing a calcination treatment after forming a solid electrolyte layer on the surface of the active material. The calcination treatment can remove the organic source material and reduce the interface contact resistance between the solid electrolyte layer and the active material, thereby promoting the fusion of the solid electrolyte layer and the active material. It is understood that the calcination treatment is carried out under a protective gas atmosphere. Optionally, the temperature of the calcination treatment is 150°C to 300°C. For example, the temperature of the calcination treatment may be, but is not limited to, 150°C, 180°C, 200°C, 220°C, 250°C, 280°C, 300°C, etc. It is understood that the temperature of the calcination treatment may also be selected in the range of 150°C to 300°C. Optionally, the calcination treatment time is 4h to 20h. For example, the calcination treatment time may be, but is not limited to, 4h, 8h, 10h, 15h, 20h, etc. It is understood that the calcination treatment time may also be selected in the range of 4h to 20h. It will be appreciated that the calcination process may be carried out in a tube furnace or a box furnace.

[0049] The present application also provides a positive electrode plate, which includes a current collector and an active layer located on at least one surface of the current collector; the active layer includes the positive electrode material or the positive electrode material prepared by the method for preparing the positive electrode material.

[0050] In one embodiment, the positive electrode plate further includes a conductive layer, the conductive layer is located on the surface of the active layer, the conductive layer includes a conductive polymer, part of the conductive polymer in the conductive layer is filled in the pores of the active layer, and the electronic conductivity of the conductive polymer is greater than the electronic conductivity of the active layer. On the one hand, the conductive layer can form an electronic conductive network inside and on the surface of the active layer to improve the conductive performance of the positive electrode plate, and on the other hand, it can also protect the positive electrode material of the active layer, reduce the contact between the positive electrode material and the external environment, and help maintain the stability of the positive electrode material.

[0051] It is understood that the active layer of the positive electrode sheet has a certain porosity for interaction with the electrolyte and promoting the infiltration of the electrolyte into the positive electrode sheet. Optionally, the porosity of the active layer is 15% to 30%. Optionally, the porosity of the active layer is 15%, 18%, 20%, 25%, 28%, 30%, etc. It is understood that the porosity of the active layer here refers to the porosity of the active layer before filling the conductive polymer.

[0052] It can be understood that the conductive layer is located on the surface of the active layer, which can be expressed as the conductive layer is located on a portion of the surface of the active layer, or can be expressed as the conductive layer is located on the entire surface of the active layer.

[0053] In one embodiment, the mass ratio of the conductive polymer to the positive electrode material is 1:(3-8). Optionally, the mass ratio of the conductive polymer to the positive electrode material can be, but is not limited to, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, etc. It is understood that the mass ratio of the conductive polymer to the positive electrode material can also be other suitable selections within the range of 1:(3-8).

[0054] It is understandable that in a conventional positive electrode sheet, a certain amount of conductive agent is often added to the slurry of the positive electrode sheet in order to improve the conductivity of the positive electrode sheet. In the present application, the use of a conductive polymer can reduce the amount of conductive agent used in a conventional positive electrode sheet and improve the conductivity of the positive electrode sheet.

[0055] In one embodiment, the electronic conductivity of the conductive polymer is 0.1×10 -3 ~10×10 -3 S / cm. Optionally, the electronic conductivity of the conductive polymer is 0.1×10 -3 , 0.5×10 -3 , 1×10 -3 , 2×10 -3 , 5×10 -3 , 8×10 -3 , 10×10 -3 wait.

[0056] In one embodiment, the porosity of the active layer filled with the conductive polymer is 10% to 25%. Optionally, the porosity of the active layer filled with the conductive polymer is 10%, 12%, 15%, 18%, 20%, 22%, 25%, etc. In one embodiment, the thickness of the portion of the conductive layer located above the surface of the active layer is 2 μm to 10 μm. Optionally, the thickness of the portion of the conductive layer located above the surface of the active layer is 2 μm, 5 μm, 8 μm, 10 μm, etc.

[0057] In one embodiment, the conductive polymer includes at least one of polypyrrole, polyaniline, polythiophene, polyacetylene and derivatives thereof. Optionally, the conductive polymer includes poly-3,4-ethylenedioxythiophene.

[0058] Optionally, the weight average molecular weight of the conductive polymer is 2,000-10,000.

[0059] The present application also provides a method for preparing a positive electrode sheet. The method for preparing a positive electrode sheet comprises the following steps: transferring a slurry containing the above-mentioned positive electrode material or a positive electrode material prepared by the above-mentioned method for preparing a positive electrode material to at least one surface of a current collector and curing it, thereby forming an active layer on the corresponding surface of the current collector.

[0060] In one embodiment, after forming the active layer, the method further includes: contacting a solution containing a conductive polymer monomer and an initiator with the surface of the active layer, and then performing an initiation treatment to polymerize the conductive polymer monomer into a conductive polymer, wherein the electronic conductivity of the conductive polymer is greater than the electronic conductivity of the active layer.

[0061] In the present application, a solution containing a conductive polymer monomer and an initiator is brought into contact with the surface of the active layer, and then an initiation treatment is performed to polymerize the conductive polymer monomer in situ into a conductive polymer, so that a conductive layer can be formed in situ on the surface of the active layer. And when the solution contacts the surface of the active layer, the solution can penetrate into the pores of the active layer, so that the conductive polymer obtained by initiation can be filled in the pores of the active layer. At this time, the interface between the conductive polymer and the positive electrode material can be effectively improved, the interface impedance can be reduced, and the conductive polymer can increase the speed of the redox reaction, alleviate the progress of the interface polarization, and thus improve the performance of the battery.

[0062] It is understood that the initiation treatment is to use the initiation conditions corresponding to the initiator to perform the treatment. For example, the initiator may be a photoinitiator, and the initiation may be performed by ultraviolet light irradiation to polymerize the conductive polymer monomer into the conductive polymer.

[0063] In one embodiment, the conductive polymer monomer includes one or more of 3,4-ethylenedioxythiophene, pyrrole, aniline and acetylene.

[0064] In one embodiment, the mass ratio of the initiator to the conductive polymer monomer is 1:(8-15). Optionally, the mass ratio of the initiator to the conductive polymer monomer is 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, etc.

[0065] In one embodiment, the solution containing the conductive polymer monomer and the initiator also includes a functional additive to improve the performance of the conductive polymer. Optionally, the functional additive is polyurethane acrylate, which has an urethane bond and can form a variety of hydrogen bonds between molecular chains, which is beneficial to the initiation process, making the initiation reaction more stable and making the performance of the obtained conductive polymer more stable.

[0066] It is understood that the solvent in the solution containing the conductive polymer monomer and the initiator may be, but is not limited to, siloxane.

[0067] In one embodiment, contacting the solution containing the conductive polymer monomer and the initiator with the surface of the active layer may be transferring the solution to the active layer of the positive electrode plate. At this time, the solution is partially filled into the pores of the active layer by capillary action, and then partially filled into the pores of the active layer by initiation treatment.

[0068] The present application also provides a secondary battery, which includes the positive electrode sheet or the positive electrode sheet prepared by the method for preparing the positive electrode sheet.

[0069] The present application also provides a battery module, which includes the secondary battery mentioned above.

[0070] The present application also provides a battery pack, which includes the secondary battery or the battery module.

[0071] The present application also provides an electric device, which includes at least one of the secondary battery, the battery module and the battery pack.

[0072] Hereinafter, the secondary battery will be described with reference to the relevant drawings.

[0073] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0074] [Positive electrode]

[0075] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.

[0076] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0077] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material on a polymer material substrate. Optionally, the metal material may include but is not limited to one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. Optionally, the polymer material substrate may include but is not limited to one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0078] In some embodiments, when the secondary battery is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates of olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and their modified compounds. Optionally, lithium cobalt oxide includes LiCoO 2 Lithium nickel oxide includes LiNiO 2 Lithium manganese oxides include LiMnO 2 and LiMn 2 O 4 At least one of the following. Lithium nickel cobalt manganese oxide includes LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM 523 )、LiNi0.5 Co 0.25 Mn 0.25 O 2 (NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (NCM 622 ) and LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM 811 ) at least one of the following. Lithium nickel cobalt aluminum oxide includes LiNi 0.85 Co 0.15 Al 0.05 O 2 Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. Optionally, the lithium iron phosphate includes LiFePO 4 (LFP). Lithium manganese phosphate includes LiMnPO 4 .

[0079] In some embodiments, when the secondary battery is a sodium ion battery, the positive electrode active material may adopt a positive electrode active material for sodium ion batteries known in the art. As an example, the positive electrode active material may be used alone or in combination of two or more. Among them, the positive electrode active material may be selected from sodium iron composite oxides, sodium cobalt composite oxides, sodium chromium composite oxides, sodium manganese composite oxides, sodium nickel composite oxides, sodium nickel titanium composite oxides, sodium nickel manganese composite oxides, sodium iron manganese composite oxides, sodium nickel cobalt manganese composite oxides, sodium iron phosphate compounds, sodium manganese phosphate compounds, sodium cobalt phosphate compounds, Prussian blue materials, polyanion materials, etc., but the present application is not limited to these materials, and the present application may also use other traditionally known materials that can be used as positive electrode active materials for sodium ion batteries. Optionally, the sodium iron composite oxide includes NaFeO 2 . Sodium cobalt composite oxides include NaCoO 2 . Sodium chromium composite oxides include NaCrO 2 Sodium manganese composite oxides include NaMnO 2 . Sodium nickel composite oxides include NaNiO 2 . Sodium nickel titanium composite oxide includes NaNi 1 / 2 Ti 1 / 2 O 2 Sodium nickel manganese composite oxides include NaNi 1 / 2 Mn 1 / 2 O 2. Sodium iron manganese composite oxide includes Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O 2 Sodium nickel cobalt manganese composite oxides include NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 Sodium iron phosphate compounds include NaFePO 4 Sodium manganese phosphate compounds include NaMnPO 4 Sodium cobalt phosphate compounds include NaCoPO 4 The polyanion material includes at least one of phosphate, fluorophosphate, pyrophosphate and sulfate.

[0080] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0081] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0082] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and the positive electrode sheet can be obtained after drying, cold pressing and other processes. Optionally, the solvent includes N-methylpyrrolidone.

[0083] [Negative electrode]

[0084] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material. The negative electrode sheet may be the negative electrode sheet described above.

[0085] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0086] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material on a polymer material substrate. Optionally, the metal material includes at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. The polymer material includes at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0087] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0088] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), carboxymethyl chitosan (CMCS), polyamide-imide (PAI), polyethyleneimine (PEI), polyimide (PI), and polytert-butyl acrylate-triethoxyvinylsilane (TBATEVS).

[0089] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0090] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener. Optionally, the thickener includes sodium carboxymethyl cellulose (CMC-Na).

[0091] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and the negative electrode sheet can be obtained after drying, cold pressing and other processes. Optionally, the solvent includes deionized water.

[0092] [Electrolyte]

[0093] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.

[0094] In some embodiments, the electrolyte includes an electrolyte salt and a solvent.

[0095] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0096] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0097] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0098] [Isolation film]

[0099] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0100] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0101] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0102] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0103] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0104] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0105] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0106] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0107] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0108] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0109] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0110] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0111] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited to these. For example, mobile devices include mobile phones, laptop computers, etc. Electric vehicles include pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0112] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0113] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0114] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0115] Example

[0116] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0117] In the following examples and comparative examples, the weight average molecular weight of poly(3,4-ethylenedioxythiophene) is 2000-10000, the weight average molecular weight of polypyrrole is 2000-10000, the weight average molecular weight of polyaniline is 2000-10000, and the weight average molecular weight of polyacetylene is 2000-10000.

[0118] Example 1

[0119] (1) Preparation of positive electrode materials.

[0120] ① LiFePO 4 The powder was placed in a fluidized bed reactor, the reaction chamber was evacuated and argon was introduced for atmosphere purge, and the gas flow rate was controlled to make LiFePO 4 Powder can be dispersed. LiFePO 4 The electrochemical window of the powder is 2.5V~3.7V.

[0121] ②In an argon atmosphere at 200℃, disperse LiFePO 4 The powder is sequentially introduced into the gas phase of lithium tert-butyl alcohol, gas phase of fluoroethylene carbonate and gas phase of triethylindium to complete a cycle. 4 The surface of the powder forms a layer of chemical composition Li 3 InF 6 The solid electrolyte layer of the material is formed in one cycle, and the thickness of the solid electrolyte layer formed in one cycle is 0.1nm. Among them, the injection pulses of gas-phase lithium tert-butyl alcohol, gas-phase fluoroethylene carbonate and gas-phase triethyl indium are 3s, 6s and 1s respectively. After each injection, the reaction chamber is purged with argon gas, and the purge time is 15s each time.

[0122] ③ Perform multiple cycles to form a solid electrolyte layer of corresponding thickness. In this embodiment, the thickness of the solid electrolyte layer is 2 nm, that is, 20 cycles are performed.

[0123] ④ In LiFePO 4 After the solid electrolyte layer is formed on the surface of the powder, the powder is calcined in an argon atmosphere at a temperature of 260° C. for 10 hours. After calcination, the powder is cooled to obtain the positive electrode material in this embodiment.

[0124] (2) Preparation of positive electrode sheets.

[0125] ① The positive electrode material and the binder polyvinylidene fluoride (PVDF) in this embodiment are stirred and mixed evenly in a weight ratio of 95:5 to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain a positive electrode sheet pre-finished product with an active layer.

[0126] ② Add siloxane to 3,4-ethylenedioxythiophene, and then add polyurethane acrylate, wherein the mass ratio of siloxane, 3,4-ethylenedioxythiophene, and polyurethane acrylate is 18:1:5. Then add the photoinitiator 2-hydroxy-2-methyl-phenylacetone, and the mass ratio of the photoinitiator to 3,4-ethylenedioxythiophene is 1:10. , obtain a solution, pour the solution on the active layer of the pre-finished positive electrode sheet, allow the solution to penetrate into the pores of the active layer through capillary force, and then cure it under ultraviolet light for about 8s to form a conductive polymer, part of which is located on the surface of the active layer, and part of which forms a conductive network in the pores of the active layer to obtain a positive electrode sheet. Among them, the mass ratio of the conductive polymer to the positive electrode material is 1:18.

[0127] (2) Preparation of negative electrode sheets.

[0128] The negative electrode active material artificial graphite, the conductive agent carbon black, and the binder polyvinylidene fluoride (PVDF) are dissolved in the solvent deionized water in a weight ratio of 96.0:2.0:2.0, and the mixture is evenly mixed to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode collector copper foil once or multiple times, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.

[0129] (3) Preparation of electrolyte.

[0130] In an argon atmosphere glove box, H 2 O<0.1ppm, O 2 <0.1ppm, mix the organic solvent ethylene carbonate (EC) / ethyl methyl carbonate (EMC) in a volume ratio of 3 / 7, add 12.5% ​​LiPF 6 The lithium salt is dissolved in an organic solvent and stirred evenly to obtain an electrolyte.

[0131] (4) Use polypropylene film as the isolation film.

[0132] (5) Preparation of lithium-ion batteries.

[0133] The negative electrode shell, negative electrode plate, isolation film, positive electrode plate, gasket, spring and positive electrode shell are placed in order, 120uL of electrolyte is added during the placement process, and the battery is compacted and allowed to stand for 2h to obtain a lithium-ion battery.

[0134] Embodiments 2 to 23

[0135] Compared with Example 1, the differences of Examples 2 to 23 are that the material and thickness of the solid electrolyte layer, the conductive polymer and the amount used are different. The specific materials and thickness of the solid electrolyte layer, the conductive polymer and the amount used in Examples 2 to 23 are shown in Table 1.

[0136] Wherein, the M source in Examples 2 and 3 is yttrium tris(2,2,6,6-tetramethyl-3,5-heptanedione) and scandium acetate, respectively.

[0137] In Example 13, the second step of the positive electrode plate is: the concentration of the ammonium persulfate solution is 0.63g / ml, an equal volume of ethanol and one-tenth of hydrochloric acid are added to form a solution as an initiator system, the volume ratio of pyrrole to benzene is 1:3 as a monomer solution, and the volume ratio of the monomer solution to the initiator system solution is 4:1. After the monomer solution is stirred evenly, the initiator system is added and poured onto the active layer of the pre-finished positive electrode plate for in-situ polymerization and curing.

[0138] In Example 14, the second step of the positive electrode plate is: using ammonium persulfate as an oxidant and a molar ratio of ammonium persulfate to aniline monomer of 1.0, adding an ammonium persulfate initiator system solution to the aniline monomer solution, pouring it on the active layer of the positive electrode plate pre-finished product, and performing in-situ polymerization and curing. The initiator system ratio is the same as that in Example 13.

[0139] In Example 15, the second step of the positive electrode is: using Ti(OBu)4-Al Et3 system to catalyze the synthesis of Nd(P 507 ), n-butanol, and then Al(C 2 H 5 ) 3 , n-butanol: Nd: Al is 4:1:6, the solvent is hydrogenated gasoline, poured on the active layer of the positive electrode pre-finished product, and in-situ polymerization and curing are carried out.

[0140] Comparative Example 1

[0141] Compared with Example 1, the difference of this comparative example is that the steps of preparing the positive electrode sheet are:

[0142] The positive electrode material, the binder polyvinylidene fluoride (PVDF), and the conductive polymer poly (3,4-ethylenedioxythiophene) are mixed in a weight ratio of 90:5:5, dispersed in NMP, stirred and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain a positive electrode sheet.

[0143] Comparative Example 2

[0144] Compared with Example 1, the difference of this comparative example is that the positive electrode material is an active material having no solid electrolyte layer formed on the surface.

[0145] Comparative Example 3

[0146] Compared with Example 1, the difference of this comparative example is that no conductive polymer is introduced into the positive electrode plate.

[0147] Comparative Example 4

[0148] Compared with Example 1, the difference of this comparative example is that the positive electrode material is an active material without forming a solid electrolyte layer on the surface, and the positive electrode plate does not introduce a conductive polymer.

[0149] Comparative Example 5

[0150] Compared with Example 1, the difference of this comparative example is that the thickness of the solid electrolyte layer is 0.2 nm.

[0151] Comparative Example 6

[0152] Compared with Example 1, the difference of this comparative example is that the thickness of the solid electrolyte layer is 10 nm.

[0153] Comparative Example 7

[0154] Compared with Example 1, the difference in this comparative example is that the mass ratio of the conductive polymer to the positive electrode material is 1:2.

[0155] Comparative Example 8

[0156] Compared with Example 1, the difference in this comparative example is that the mass ratio of the conductive polymer to the positive electrode material is 1:9.

[0157] Test Case

[0158] Battery capacity retention rate test: At 25°C, the batteries corresponding to the examples and comparative examples were charged to 4.5V at a constant current of 1 / 3C, then charged to a current of 0.05C at a constant voltage of 4.5V, left for 5 minutes, and then discharged to 2.8V at a constant current of 1 / 3C. The obtained capacity was recorded as the initial capacity C. 0 Repeat the above steps and record the discharge capacity C of the battery after the nth cycle. n , then the battery capacity retention rate P after each cycle n =C n / C 0 *100%. The capacity retention rate of the battery after 100 test cycles, i.e. P 100 The test results are shown in Table 1.

[0159] Battery AC impedance test: The positive electrode sheet, separator, and 120uL electrolyte in the embodiment and comparative example are assembled into a symmetrical battery with a positive electrode, and placed in a 25°C constant temperature box for 2h to ensure the infiltration of the electrolyte. The AC impedance test uses an electrochemical workstation impedance test module, voltage perturbation mode PEIS, perturbation voltage 5mV, frequency range 200kHZ~30mHZ, 0~5V voltage range, 0~5V voltage protection, and the test data is plotted with the negative of the imaginary part of the impedance as the ordinate and the real part as the abscissa to draw the impedance spectrum.

[0160] Impedance test data fitting processing: The impedance data of the embodiment and the comparative example were fitted using Z-fit software, and the fitting circuit was selected as R s +C 1 / R SEI +C 2 / R ct +W, where R s is the ohmic impedance, which is mainly related to the conductivity of the positive electrode material, R ct It is the charge transfer impedance, which mainly reflects the rate of lithium ion insertion and extraction in the positive electrode material. The fitting judgment requirement is: the error is less than 5%, and the intersection point with the real part should be consistent with the R obtained by fitting. s The deviation is less than 5%. Only the fitting results that meet the above requirements can be selected and accepted. ct With R s The extracted data are recorded in Table 1.

[0161] Porosity test: Adopt Archimedes principle - gas expansion displacement method, use small molecule inert gas as medium, calculate the volume of gas displaced by the sample in the test cavity through the ideal gas state equation: PV = nRT, so as to accurately measure the real volume of the sample, porosity = (V1-V2) / V1*100%, V1: apparent volume of the sample, V2: real volume of the sample. Among them, the small molecule inert gas is He or N 2 The true volume of the sample includes the volume of the closed pores.

[0162] Electronic conductivity test: The two-probe method is used to directly measure the overall resistivity of the electrode. Conductivity = L / (R*A), where L is the thickness, R is the resistance, and A is the contact area.

[0163] Table 1

[0164]

[0165]

[0166] It can be seen from Table 1 that the introduction of the solid electrolyte layer and / or the conductive polymer can enable the battery to have a higher capacity retention rate.

[0167] Specifically, it can be seen from Example 1 and Comparative Examples 2 to 6 that the battery corresponding to the positive electrode material having a solid electrolyte layer of appropriate thickness has a higher capacity retention rate. It can be seen from Example 1 and Comparative Examples 7 to 8 that the appropriate amount of conductive polymer is conducive to improving the capacity retention rate of the battery.

[0168] In Example 1, the conductive polymer is in-situ cured in the positive electrode sheet, and in Comparative Example 1, the conductive polymer is directly added to the positive electrode slurry. It can be seen from Example 1 and Comparative Example 1 that the battery obtained by in-situ curing has a higher capacity retention rate.

[0169] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode material, characterized in that: The invention comprises an active material and a solid electrolyte layer coated on the surface of the active material; the electrochemical window of the solid electrolyte layer is larger than the electrochemical window of the active material; the electrochemical window of the solid electrolyte layer is ≥5V; the solid electrolyte layer comprises a chemical composition of Li a MX a+3 A material wherein 1≤a≤6, M is selected from cations of one or more of the following elements: Al, Ga, In, Y, Zr, Nb, Sc, Ti, Mn, and La series elements; and X is selected from anions containing one or more of the following elements: halogen, S, O, and P.

2. The positive electrode material according to claim 1, characterized in that The thickness of the solid electrolyte layer is 0.5 nm to 5 nm.

3. The positive electrode material according to claim 1, characterized in that The thickness of the solid electrolyte layer is 1 nm to 2 nm.

4. The positive electrode material according to claim 1, characterized in that The lithium ion conductivity of the solid electrolyte layer is ≥0.8×10 -4 S / cm.

5. The positive electrode material according to claim 1, characterized in that M is a +3 valent cation.

6. The positive electrode material according to claim 1, characterized in that M includes Al 3+ , Ga 3+ 、In 3+ , Y 3+ 、Zr 3+ , Nb 3+ Sc 3 + 、Ti 3+ , Mn 3+ , Er 3+ , Tb 3+ , Yb 3+ 、Lu 3+ ,La 3+ and Ho 3+ One or more of .

7. The positive electrode material according to claim 1, characterized in that X includes F - , Cl - Br - ,I - , S 2- , O 2- and PO4 - One or more of .

8. The positive electrode material according to claim 1, characterized in that The solid electrolyte layer includes at least one of Li3InF6, Li3YF6, Li3ScF6, Li3MnF6, Li3ZrF6, Li3InCl6, Li3YCl6, Li3ScCl6, Li3MnCl6 and Li3ZrCl6.

9. A method for preparing a positive electrode material, characterized in that: The steps include: A solid electrolyte layer is formed on the surface of the active material; wherein the electrochemical window of the solid electrolyte layer is greater than the electrochemical window of the active material; the electrochemical window of the solid electrolyte layer is greater than or equal to 5V; the solid electrolyte layer includes a chemical composition of Li a MX a+3 A material wherein 1≤a≤6, M is selected from cations of one or more of the following elements: Al, Ga, In, Y, Zr, Nb, Sc, Ti, Mn, and La series elements; and X is selected from anions containing one or more of the following elements: halogen, S, O, and P.

10. The method for preparing the positive electrode material according to claim 9, characterized in that: A solid electrolyte layer is formed on the surface of the active material using an atomic deposition method.

11. The method for preparing the positive electrode material according to claim 10, characterized in that: Forming a solid electrolyte layer on the surface of the active material includes the following steps: In a protective gas atmosphere, a gas phase Li source, a gas phase X source and a gas phase M source are sequentially introduced into the dispersed active material to form a gas phase Li a MX a+3 Solid electrolyte layer of material.

12. The method for preparing the positive electrode material according to claim 11, characterized in that: The temperature of the protective gas atmosphere is 150°C to 250°C.

13. The method for preparing the positive electrode material according to claim 11, characterized in that: In the intervals between sequentially introducing the gas-phase Li source, the gas-phase X source and the gas-phase M source, the reaction system is purged with a protective gas.

14. The method for preparing the positive electrode material according to claim 13, characterized in that: Each purge lasts 10s~20s.

15. The method for preparing the positive electrode material according to claim 11, characterized in that: The ratio of the injection pulses of the gas phase Li source, the gas phase X source and the gas phase M source is a:(a+3):

1.

16. The method for preparing a positive electrode material according to any one of claims 9 to 15, characterized in that: Also includes: After the solid electrolyte layer is formed on the surface of the active material, a calcination treatment is performed.

17. The method for preparing the positive electrode material according to claim 16, characterized in that: The calcination temperature is 150°C to 300°C.

18. The method for preparing the positive electrode material according to claim 16, characterized in that: The calcination time is 4h~20h.

19. A positive electrode plate, characterized in that: It comprises a current collector and an active layer located on at least one surface of the current collector; the active layer comprises the positive electrode material according to any one of claims 1 to 8 or the positive electrode material prepared by the preparation method of the positive electrode material according to any one of claims 9 to 18.

20. The positive electrode sheet according to claim 19, characterized in that: It also includes a conductive layer, which includes a conductive polymer. The conductive layer is located on the surface of the active layer and part of the conductive polymer in the conductive layer is filled in the pores of the active layer. The electronic conductivity of the conductive polymer is greater than the electronic conductivity of the active layer.

21. The positive electrode sheet according to claim 20, characterized in that: The positive electrode sheet meets one or more of the following characteristics: (1) The mass ratio of the conductive polymer to the positive electrode material is 1:(3-8); (2) The electronic conductivity of the conductive polymer is 0.1×10 -3 ~10×10 -3 S / cm; (3) The porosity of the active layer filled with the conductive polymer is 10% to 25%; (4) The thickness of the portion of the conductive layer located above the surface of the active layer is 2 μm to 10 μm; (5) The conductive polymer includes at least one of polypyrrole, polyaniline, polythiophene, polyacetylene and derivatives thereof.

22. A method for preparing a positive electrode sheet, characterized in that: The steps include: A slurry of a positive electrode material comprising the positive electrode material according to any one of claims 1 to 8 or prepared by the method for preparing a positive electrode material according to any one of claims 9 to 18 is transferred to at least one surface of a current collector and solidified to form an active layer on the corresponding surface of the current collector.

23. The method for preparing a positive electrode sheet according to claim 22, characterized in that: After forming the active layer, the method further comprises: A solution containing a conductive polymer monomer and an initiator is brought into contact with the surface of the active layer, and then an initiation treatment is performed to polymerize the conductive polymer monomer into a conductive polymer, wherein the electronic conductivity of the conductive polymer is greater than the electronic conductivity of the active layer.

24. A secondary battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to any one of claims 19 to 21 or a positive electrode sheet prepared by the preparation method of the positive electrode sheet according to any one of claims 22 to 23.

25. A battery module, characterized in that: Includes the secondary battery as claimed in claim 24.

26. A battery pack, characterized in that: Includes the secondary battery according to claim 24 or the battery module according to claim 25.

27. An electrical device, characterized in that: Includes at least one of the secondary battery of claim 24, the battery module of claim 25, and the battery pack of claim 26.

Citation Information

Patent Citations

  • Positive active material for lithium-ion secondary battery, positive electrode for lithium-ion secondary battery, and lithium-ion secondary battery

    CN105280911A

  • Methods and apparatus for resource allocation and feedback in vehicle to vehicle communication

    CN111316585A